The Origins of Fears of Compassion: Shame and Lack of Safeness Memories, Fears of Compassion and Psychopathology. Issue 8 (17th November 2017) - Matos, Marcela; Duarte, Joana; Pinto-Gouveia, José
ABSTRACT: Empirical and clinical research suggests that some individuals find self-generating compassion and receiving compassion from others difficult and aversive. However, it is unclear how these fears of compassion are linked to early experiences and to psychopathological symptoms. This study explores the relationship between shame traumatic memories, centrality of shame memories, early memories of warmth and safeness, fears of compassion, and depression, anxiety and paranoid symptoms. Participants were 302 individuals from the general community population, who completed self-report measures of fears of compassion, shame memories, early affiliative memories, and psychopathology. Shame traumatic and central memories were positively associated with fears of compassion for self, for others and from others, whereas early memories of warmth and safeness were negatively related to such fears. Path analyses revealed that fears of compassion for self and of receiving compassion from others mediated the effects of shame traumatic memory, centrality of shame memory and early memories of warmth and safeness on depressive, anxious and paranoid symptoms. These findings have implications for therapeutic interventions as these fears, as well as the negative shame-based emotional memories fuelling them, may need to be addressed in therapy to assist patients in self-generating and receiving compassion.